(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazione. SOMMARIO: 1. Breve premessa sull’insegnamento della religione in Europa - 2. La Corte Europea dei Diritti Umani e l’istruzione religiosa - 3. Scuola e religione in Turchia - 4. Alevismo e istruzione religiosa: il caso “Hasan e Eylem Zengin c. Turchia” - 5. La reazione alle sentenze in Turchia e in Europa - 6. Conclusione.ABSTRACT: Religious education has become a topic of great interest in the last two decades in Turkey as the result of the rulings of national and international courts and the pressure by non-Muslim communities for the recognition of their rights. The Alevi’s struggle for religious education to ensure respect for parental beliefs, in line with the European Convention on Human Rights, has attracted great attention through the applications of some Alevi citizens to the European Court of Human Rights (ECtHR), which contributed to the raising of public debate on the relationship between the State, the education system and religion. This work is aimed at understanding the position taken by the Strasbourg Court on religious education in Turkey in 2007 by analysing the pioneering case Hasan and Eylem Zengin v. Turkey, which set the case law, and reflecting on the impact that the judgment had both in Turkey and in Europe.